Computer control in the process industries - Roffel, Brian; Chin, Patrick (Chelsea, Mich. : Lewis Publishers, 1987)
The book tries to promote the use of advanced control techniques by taking the reader from basic theory to practical implementation.
System requirements for computer disk: PC and Lotus 1-2-3 program.
Includes index.
Bibliography: p. 237-245.
ii 15/01/2019
Loans
Keywords: Process control